'Would you prefer not to?' Resetting/resistance across literature, culture, and organizations. Issue 2 (15th March 2019) - Benozzo, Angelo; Koro-Ljungberg, Mirka; Adamo, Sergia
ABSTRACT: In this paper we put the concepts of reset, aprosdoketon and minor gesture to work in the context of organizational narratives. In particular we engage with two iconic characters of the genre of organizational fiction, Don Draper in the context of Mad Men TV series and the copyist, who is the main character of Bartleby, the Scrivener by Herman Melville. Through a series of textual and performative writings we explore the possibility of setting and resetting organizational narratives/genre. Moreover, we explore what happens when fictional characters from a TV series and a novel (Bartleby and Don Draper) meet us – three scholars working in an array of different fields (literary, methodology, education and organization studies) and how this meeting and interaction shapes our understandings of work, culture, and organizations.